Europeanisation of inequality and European reference groups - Christopher T. Whelan; Bertrand Maître (The Economic and Social Research Institute (ESRI), 2008)
In this paper we take advantage of the recent availability of EU-SILC data to contribute to the recent debate relating to the Europeanisation of reference groups. Our analysis addresses both weak and strong versions of the thesis. The former proposes that common standards of what is an acceptable level of participation in one's own society emerge as a consequence of knowledge of conditions in other societies. The latter argues that people increasingly perceive themselves as part of a larger European stratification. Our analysis leads us to reject both versions of the thesis. Material deprivation rather than having a uniform effect is highly dependent on national context. In circumstances where the Europeanisation of inequality is raising issues relating to both national and transnational forms of legitimacy, it is important to understand that there is no necessary relationship between such Europeanisation and the Europeanisation of reference groups.
Keywords: 330; Europeanisation of inequality; reference groups; deprivation; economic stress; legitimacy; Soziale Lage; Soziale Ungleichheit; EU-Erweiterung; EU-Staaten